Evidence of the Importance of Nox4 in Production of Hypertension in Dahl Salt-Sensitive Rats. Issue 2 (February 2016) - Cowley, Allen W.; Yang, Chun; Zheleznova, Nadezhda N.; Staruschenko, Alexander; Kurth, Theresa; Rein, Lisa; Kumar, Vikash; Sadovnikov, Katherine; Dayton, Alex; Hoffman, Matthew; Ryan, Robert P.; Skelton, Meredith M.; et al.
Abstract : This study reports the consequences of knocking out NADPH (nicotinamide adenine dinucleotide phosphate) oxidase 4 ( Nox4 ) on the development of hypertension and kidney injury in the Dahl salt-sensitive (SS) rat. Zinc finger nuclease injection of single-cell SS embryos was used to create an 8 base-pair frame-shift deletion of Nox4, resulting in a loss of the ≈68 kDa band in Western blot analysis of renal cortical tissue of the knock out of Nox4 in the SS rat (SS Nox4−/− ) rats. SS Nox4−/− rats exhibited a significant reduction of salt-induced hypertension compared with SS rats after 21 days of 4.0% NaCl diet (134±5 versus 151±3 mm Hg in SS) and a significant reduction of albuminuria, tubular casts, and glomerular injury. Optical fluorescence 3-dimensional cryoimaging revealed significantly higher redox ratios (NADH/FAD [reduced nicotinamide adenine dinucleotide/flavin adenine dinucleotide]) in the kidneys of SS Nox4−/− rats even when fed the 0.4% NaCl diet, indicating greater levels of mitochondrial electron transport chain metabolic activity and reduced oxidative stress compared with SS rats. Before the development of hypertension, RNA expression levels of Nox subunits Nox2, p67 phox, and p22 phox were found to be significantly lower ( P <0.05) in SS Nox4−/− compared with SS rats in the renal cortex. Thus, the mutation of Nox4 seems to modify transcription of several genes in ways that contribute to the protective effects observed in the SS Nox4−/− rats. We conclude that the reduced renal injury and attenuated blood pressure response to high salt in the SS Nox4−/− rat could be the result of multiple pathways, including gene transcription, mitochondrial energetics, oxidative stress, and protein matrix production impacted by the knock out of Nox4. Abstract : Supplemental Digital Content is available in the text.